Django unchained [videorecording (Blu-Ray)] - Foxx, Jamie; Waltz, Christoph, 1956-; DiCaprio, Leonardo; Washington, Kerry, 1977-; Jackson, Samuel L.; Sher, Stacey; Hudlin, Reginald; Savone, Pilar; Tarantino, Quentin; Tarantino, Quentin (Anchor Bay Entertainment, 2013)
Django, a former slave turned hired gun, heads back to the plantation to free his wife, Broomhilda, from the tyrannical plantation owner Calvin Candie, with the help of a German bounty hunter, Dr. King Shultz.